The importance of soils in predicting the future of plant habitat suitability in a tropical forest - G. Zuquim; F. R. C. Costa; H. Tuomisto; G. M. Moulatlet; F. O. G. Figueiredo (Springer International Publishing, 2022)
Aims
Assessment of the future of biodiversity under climate change has been based on climate-only models. We investigated the effects of including soil information when predicting future suitable areas for selected plant species in Amazonia.
Methods
We modelled current and future suitable habitats for 35 plant species and compared results of climate-only models with those obtained when climatic and edaphic variables were included. We considered six climatic scenarios for 2050 using different algorithms and projections of atmospheric CO2 concentration.
Results
Twenty-five species distribution models had an AUC > 0.69. Out of those, edaphic variables had the greatest contribution in 11 species models, while climatic variables were more important for 14 species. The inclusion of soil variables affected the size and shape of predicted suitable areas, especially in future models. For nearly half of the species, the size of future suitable areas were smaller in climate+soil models than predicted by climate-only models. Area reduction was more extreme in future scenarios with the higher level of CO2 concentration.
Conclusions
Our results highlight the importance of moving beyond climatic scenarios when modelling biodiversity responses to climate change. Failure to include soils in the models can overestimate future habitat suitability for many plant species.